Detection of Anaemia in Some Ruminant Species in Alkhalis City of Diyala Province, Iraq - Ismail, Muna Muhammed (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was designed to measure the percent  of anemia in some ruminant   animals cow, sheep and goat in Alkhalis city of Diyala/ Iraq. Sixty nine blood samples(5ml/animal) were collected from jugular vein of some ruminant animals (cow, sheep and goat) by disposable syringe washed with anticoagulant(heparin), during blood sample collection district peasant association; age, sex and case history of each animal were recorded  for two months   November and December 2021 from different area of Alkhalis city (Altahuella, Hibhib, Altamor, Alsndia; Alsharqia; Aljdida and Alaswad) the collected blood samples were put in ice container and analyzed during 24 hr after collection at physiology laboratory/college of veterinary medicine/Diyala university. The results showed significant decrease of PCV, RBC and Hb  of anemic: cow in prevalence( 11%,11%,11%) , sheep( 34%,34%,55%) and goat(27%,27%,36%) . On the other hand the MCV, MCH and MCHC values illustrated significant decrease in sheep and goat while cow appeared significantly decrease in MCV only.   In conclusion; the ruminant animals sheep and goat suffering from anemia more than cow i.e sheep and goat more sensitive to bad management  beside; The type of anemia in cow microcytic normochromic, while the type of anemia in sheep and goat microcytic hypochromic.
Keywords: Anaemia; Cattle; Diyala province; Goat; Prevalence; Sheep